Kagiso Trust : deciding its future - Beswick, Claire; Rijamampianina, Rasoava ([London] : SAGE, 2016)
In November 2014, Kagiso Trust (KT) was at an important crossroads. Anti-apartheid struggle icons such as Dr Beyers Naude and Archbishop Desmond Tutu had established the organisation with European Union (EU) funds in the 1980s to promote the struggle against apartheid. Since then, KT had become a professional social development agency, funded in part by dividends from Kagiso Tiso Holdings (KTH), a black economic empowerment investment house that KT had helped to establish. Now, KT was on the brink of tripling its investment income by virtue of dividends from a black economic empowerment (BEE) deal it had entered into with banking group FirstRand in 2004. KT's trustees had to consider how best to use these additional funds.
Originally Published in: Beswick, C., & Rijamampianina, R. (2015). Kagiso Trust: Deciding its Future. WBS-2015-7. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Dividends -- Case studies; Corporations -- Finance -- Case studies; Business planning -- Case studies